Development of a physiologically relevant and easily scalable LUHMES cell-based model of G2019S LRRK2-driven Parkinson's disease - Barbara Calamini; Nathalie Geyer; Nathalie Huss-Braun; Annie Bernhardt; Véronique Harsany; Pierrick Rival; May Cindhuchao; Dietmar Hoffmann; Sabine Gratzer (The Company of Biologists, 2021)
Parkinson's disease (PD) is a fatal neurodegenerative disorder that is primarily caused by the degeneration and loss of dopaminergic neurons of the substantia nigra in the ventral midbrain. Mutations in leucine-rich repeat kinase 2 (LRRK2) are the most common genetic cause of late-onset PD identified to date, with G2019S being the most frequent LRRK2 mutation, which is responsible for up to 1-2% of sporadic PD and up to 6% of familial PD cases. As no treatment is available for this devastating disease, developing new therapeutic strategies is of foremost importance. Cellular models are commonly used for testing novel potential neuroprotective compounds. However, current cellular PD models either lack physiological relevance to dopaminergic neurons or are too complex and costly for scaling up the production process and for screening purposes. In order to combine biological relevance and throughput, we have developed a PD model in Lund human mesencephalic (LUHMES) cell-derived dopaminergic neurons by overexpressing wild-type (WT) and G2019S LRRK2 proteins. We show that these cells can differentiate into dopaminergic-like neurons and that expression of mutant LRRK2 causes a range of different phenotypes, including reduced nuclear eccentricity, altered mitochondrial and lysosomal morphologies, and increased dopaminergic cell death. This model could be used to elucidate G2019S LRRK2-mediated dopaminergic neural dysfunction and to identify novel molecular targets for disease intervention. In addition, our model could be applied to high-throughput and phenotypic screenings for the identification of novel PD therapeutics.